Why sanctions have not worked: Zimbabwe’s experience from 2001-2021 - Joshua Chakawa (Taylor & Francis Online., 2022)
Zimbabwe has since 2001 been under targeted sanctions imposed by the USA, European Union, Australia, Britain, New Zealand, and Canada among others. This article explores factors surrounding the failure of these sanctions to achieve their intended goals between 2001 and 2021. Arguments were drawn from investigating circumstances under which sanctions were imposed, their nature, sanctions busting methods deployed, and implications for the targets. The regime of former president Robert Mugabe and that of his successor Emmerson Mnangagwa controversially remained unmoved despite these restrictions. The ruling party, Zimbabwe African National Union Patriotic Front (ZANU-PF), deliberately failed to meet benchmarks for the removal of sanctions. To understand the relationship between sanctions and targeted regime endurance, use was made of the game theory. The study found that ruling party political elites have circumvented the effects of sanctions at a heavy cost to the populace. This research is important because it demonstrates that sanctions do not harm their targets but instead pauperise, the majority which they meant to protect and prolong the political life of the sanctioned regime. The act of sanctioning therefore needs to be reconsidered.